2008
DOI: 10.1107/s0021889808014994
|View full text |Cite
|
Sign up to set email alerts
|

Critical opalescence points to thermodynamic instability: relevance to small-angle X-ray scattering of resorcinol–formaldehyde gel formation at low pH

Abstract: Author(s) of this paper may load this reprint on their own web site or institutional repository provided that this cover page is retained. Republication of this article or its storage in electronic databases other than as specified above is not permitted without prior permission in writing from the IUCr.For further information see http://journals.iucr.org/services/authorrights.html Many research topics in condensed matter research, materials science and the life sciences make use of crystallographic methods to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Recently, carbon xerogels have also proved to be excellent alternatives to activated carbons in various processes [14][15][16]. These materials are composed of microporous interconnected sphere-like nodules, formed during the gel synthesis via a microphase separation mechanism induced by polymer growth [17]. The size of these nodules is mainly regulated by the synthesis pH [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon xerogels have also proved to be excellent alternatives to activated carbons in various processes [14][15][16]. These materials are composed of microporous interconnected sphere-like nodules, formed during the gel synthesis via a microphase separation mechanism induced by polymer growth [17]. The size of these nodules is mainly regulated by the synthesis pH [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, two other hypotheses could explain this skin phenomenon. First, SAXS measurements performed during the synthesis of low‐pH resorcinol and formaldehyde gels showed that the gel formation is driven by reaction‐induced phase separation processes . The relative velocity of the beads in oleic acid can generate friction and shear stresses at the beads surface that could locally disturb the phase separation of the gel formation and lead to such skin phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The flask was left unstirred at 70 ∘ C for precuring during 45 min. In these conditions, the gelation time is approximately 50 min, thus, after 45 min, the precured solution was not gelled and could be handled as a liquid. The flask was quenched using tap water to slow down the gelation reaction and avoid any gelation in the nozzle that would instantly plug it.…”
Section: Methodsmentioning
confidence: 99%
“…This type of reaction-induced phase separation has been directly evidenced by scattering methods in quite a few instances: in hybrid silica gels, ,, in curing polymer blends, in hybrid organic−inorganic materials, and in resorcinol−formaldehyde gels. Moreover, the fact that phase separation leads in a very natural way to the fiberlike morphologies ubiquitous to gels and many biological structures suggests that this mechanism is far more common than what is generally acknowledged. , …”
Section: Time-resolved Saxs Of Gelling Hybrid Silica Solutionsmentioning
confidence: 98%